Comparison of Two Different Endotracheal Aspiration Methods in Premature Infants - Gülsüm Kadıoğlu Şimşek; Mehmet Büyüktiryaki; Nilüfer Okur; H. Gozde Kanmaz Kutman; Fuat Emre Canpolat (Galenos Publishing House, 2019)
INTRODUCTION: The aim of our study was to compare open and closed endotracheal aspiration methods in premature infants in terms of neonatal infections and premature morbidities. METHODS: Between January 2016 and December 2016, the records of preterm infants with a birth weight under 1500 g were retrospectively reviewed in our neonatal intensive care unit. Infants in the first 72 hours of life with a need of intubation and at least 24 hours on mechanical ventilation were included in analysis. In addition to demographic and clinical data of infants, premature morbidities, total aspiration numbers and duration of respiratory support were recorded in which endotracheal aspiration method was used. RESULTS: The data of 38 infants who underwent open aspiration and 39 with closed aspiration were analyzed. Demographic findings were similar in two groups. There were no differences between the two groups in terms of total number of aspirations, extubation failure, respiratory support durations, bronchopulmonary dysplasia, ventilator-associated pneumonia and late onset neonatal sepsis. In addition, there was no difference in terms of other prematurity morbidities, hospital stay and mortality. DISCUSSION AND CONCLUSION: In our study, premature infants with birth weight less than 1500 g were not found to be associated with premature morbidities with open or closed endotracheal aspiration.